Maya : - Kundert-Gibbs, John L. (SYBEX, 2005)
The follow-up to a first edition that was named "Best book for experienced users" by 3dRender.com, this distinctive Maya Press title features all new material and striking four-color images. Each chapter focuses on a unique, prevailing topic and is written by a different pro who reveals secrets learned from working on high-visibility projects, such as "The Matrix", "Shrek 2", "Lord of the Rings", TV commercials, and games production. Designed to inform and inspire, this sophisticated book covers topics such as auto-rigging, subdivision surfaces, cloth, hair, HDRI rendering, cinematics, skin, fur, and noise. The CD features movie files of sample animations, and scene and support files from the book's projects